¿Hasta dónde estamos dispuestos a comprometernos con la libertad religiosa? - Caviglia Marconi, Alessandro (2011)
One of the main rights, internationally and currently acknowledged is the religious freedom, which let us to freely profess a religious belief without being persecuted or bothered by the State or by society sectors which they belonged to. In this article, the author assumes that in a democratic and liberal society, citizens must enjoy this right to profess their religious beliefs, even though they will result extravagant to the other members of the society. However, thisfundamental right has been permanently violated in contemporary democratic societies. This happens because of a lack of liberal culture, which might adequately separate the State from the religious sphere, or in societies where such separation has been executed however, the situation of settled conflicts may lead in new ways of tyranny.